Challenges, Coping and Resources: A Thematic Analysis of Foreign Teachers’ Experience of Cultural Adaptation in China - Yi, Su; Wu, Ning; Xiang, Xiaoqin; Liu, Liang (Frontiers in Psychology, 2020)
The aim of this study was to explore foreign teachers’ experience of cultural and life adaptation in China, including the difficulties, emotional stress and challenges they confronted, as well as the useful coping strategies and resources that facilitated their cultural adaptation. Ten foreign professors who taught in China were recruited from 3 Chinese universities. Semistructured interviews on the participants’ experience of cross-cultural adaptation in China were conducted. Thematic analysis of the transcribed dialogs was performed, and five core themes emerged: multiple challenges, mixed negative emotions, active coping and insulation, rich supportive resources, and personal traits. In the cross-cultural adaptation process in China, the main challenges for foreign teachers were language barriers, a lack of supportive relationships and conflicts in perceptions related to teaching, privacy and boundaries. Useful coping strategies included seeking interpersonal interactions that provided emotional and instrumental support, developing localized teaching models and maintaining connections with the culture of origin. Under circumstances with convenient living facilities and supportive interpersonal relationships, these strategies promoted the adaptation of foreign teachers with functional personality traits. The potential correlations among these different themes and the influence of their interactions on foreign teachers’ adaptation experience were also discussed. The themes that emerged in our study can help clinicians and university administrators develop therapy methods and support systems for foreign teachers who work in Chinese universities.